A Review on Document Retrieval from Unstructured Text - Lohbare, Sneha; Meshram, Ashwini (International Journal of Computer Sciences and Engineering, 2014)
A simple search over a document can be considered as a traditional method of searching from a single document in database. A keyword or string is considered as core element while searching where string may be strings of words, characters for any phrase. Many problems in such keyword or phrase-based searching arise when a keyword or phrase is intended to be searched in multiple documents. For the same, a solution suggested is a repetitive procedure of searching for every document. It can be helpful for limited number of copies of document. But this solution can never be considered efficient and effective in case of large number of documents in database which is supposed to be increasing continuously. Also, searching for the pattern based or the regular expression based content from the document is one of the demanding topics of research. Processing such queries requires a lot of processing time and complete indexing of data is bit difficult process.